High percentages of peripheral blood T-cell activation in childhood Hodgkin's lymphoma are associated with inferior outcome - Cai, Fengqing; Gao, Hui; Yu, Zhongsheng; Zhu, Kun; Gu, Weizhong; Guo, Xiaoping; Xu, Xiaojun; Shen, Hongqiang; Shu, Qiang (Frontiers in Medicine, 2022)
The aims of this study were to investigate the activation of T lymphocytes in peripheral blood from children with HL and to explore their roles for prognosis in HL. A cohort of fifty-two newly diagnosed with HL in children during the past ten years was enrolled for analysis in this study. Peripheral blood samples of patients were acquired before treatment in our hospital and T cells subsets were detected by a four-color flow cytometer. CD4+ T cells and CD4+/CD8+ T cell ratio decreased significantly in patients with HL vs. healthy controls. CD8+ T cells, CD3+CD4+HLA-DR+ T cells and CD3+CD8+HLA-DR+ T cells increased markedly in HL patients vs. healthy controls. Receiver operating characteristic curve analysis showed that CD3+CD4+HLA-DR+ T cells and CD3+CD8+HLA-DR+ T cells each distinguished the high-risk group from the low and intermediate-risk group. The area under the ROC curve for predicting high-risk patients was 0.795 for CD3+CD4+HLA-DR+ T cell and was 0.784 for CD3+CD8+HLA-DR+ T cell. Comparison of peripheral blood T cell subsets that responded differently to therapy showed significantly higher percentages of CD3+CD4+HLA-DR+ T cells and CD3+CD8+HLA-DR+ T cells in patients who achieved complete remission compared to those who did not achieve complete remission. In addition, high percentages of both CD3+CD4+HLA-DR+ T cells and CD3+CD8+HLA-DR+ T cells were associated with inferior event-free survival. Peripheral immune status may be related to disease severity in HL. CD3+CD4+HLA-DR+ T cells and CD3+CD8+HLA-DR+ T cells may be a novel indicator for risk-stratification of HL and may be an independent risk factor for inferior outcome in childhood HL.